Astor : the rise and fall of an American fortune - Cooper, Anderson; Howe, Katherine, 1977- (Harper, an imprint of HarperCollinsPublishers, 2023)
"The story of the Astors is an extraordinary but true tale of ambition, invention, destruction, and reinvention--and of cunning, determination, hard work, hubris, infighting, and greed. One of the wealthiest men to have ever lived, John Jacob Astor first arrived in New York in 1783 and built a fortune through a ruthless expansion of his beaver trapping business, which he grew into an empire through real estate that enriched him at the expense of Manhattan's poorest residents. In later generations, Astors ruled Gilded Age New York society--Caroline Schermerhorn Astor essentially invented it--and got into the hospitality business with the legendary Waldorf-Astoria hotel, among others. Yet for all their unimaginable success, the Astors also endured crushing tragedy and reversals of fortune. John Jacob Astor IV perished in the Titanic disaster, its most famous victim. His cousin William Waldorf Astor renounced the United States. Rifts would split siblings and pit cousins against one another, legal battles would create irreparable divides, and mansions would be built and razed, or fall into disrepair. By 2009, when Brooke Astor's son, was convicted of defrauding his elderly mother--who had herself married into the family for money--the Astor dynasty was effectively over. In this unconventional, page-turning historical biography, featuring black-and-white and color photographs, Anderson Cooper and Katherine Howe chronicle the lives of the Astors and offer a window onto the making of America itself"--Dust jacket flap.